Literature review: implementation of Musharakah Mutanaqisah partnership over the world - Wiwin Juliyanti; Yohanes K. Wibowo (Penerbit Goodwood, 2021)
Purpose: This study aimed to determine the implementation of Musharakah Mutanaqisah. Research methodology: This research method was a literature study with data obtained from previous research and theories relevant to the research topic. Results: The research results show that Musharakah Mutanaqisah in the two countries still needs to be encouraged for its development, because Murabahah still dominates it, Ba'i, ijarah and others financing, the results of the study also concluded that the implementation of Musharakah Mutanaqisah is equally an alternative in property financing in Malaysia, and homeownership loans in Indonesia. Limitations: This research only examined the application of MMP in Southeast Asia Contribution: Findings contribute that internationally, accounting for Musharakah Mutanaqisah refers to IFRS and FAS. In Malaysia, the regulations governing the accounting for Musharakah Mutanaqisah are regulated in the Malaysian Financial Reporting Standards (MFRS). ). In Indonesia, the regulations governing the accounting for Musharakah Mutanaqisah are not yet available, so they are still regulated in PSAK No. 106 (Musharakah Akad). Keywords: Musharakah Mutanaqisah partnership, Islamic bank, Sharia accounting